Needs Analysis of Comic-Based Folk Story Teaching Materials for BIPA Learners - Aulia, Nurul Lutfhi; Mulyati, Yeti; Damayanti, Vismaia S; Sundusiah, Suci (Bina Nusantara University, 2025)
The increasing demand for culturally rich and engaging materials in Indonesian for Foreign Language Speakers (BIPA) programs highlights the need for innovative teaching resources. Existing folk story materials often fail to capture learners’ interest or accommodate their linguistic levels, making language acquisition and cultural understanding more challenging. This study aims to analyze the specific educational needs of BIPA learners in relation to comic-based folk story teaching materials, as a foundational step toward developing effective instructional resources. Employing a descriptive qualitative method, data were collected through interviews and questionnaires involving 18 BIPA learners and 30 experienced instructors, along with a review of existing BIPA materials. The results show a strong preference for materials that blend simplified literary content with authentic cultural narratives in a visually engaging format. Learners and instructors identified comics as effective tools for enhancing comprehension and motivation, particularly for beginners. The study concludes that developing comic-based folk story materials addresses current pedagogical challenges in BIPA instruction while supporting intercultural learning. It recommends piloting these materials in diverse learning contexts and refining them based on learner feedback.